Analysis of Elementary School Teachers' Ability in Using ICT Media and Its Impact on the Interest to Learn of Students in Banda Aceh - Yusrizal Yusrizal; Ibnu Hajar; Samsidar Tanjung (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2019)
This study aims to determine: 1) Primary School Teachers' Ability in utilizing ICT-based learning media in Banda Aceh City; and 2) Differences in the average of students interest in learning taught by high, medium and low competence teachers in utilizing ICT-based learning media.This research is conducted in Banda Aceh City. The population in this study are public elementary schools equipped with wifi and at least B accredited consisting of 42 schools. The research method used is a quantitative method with a comparative type. Data collection techniques ae carried out by observation techniques, and questionnaires. The data analysis technique in this study uses one-way ANAVA. The results of the study show that: (1) The ability of elementary school teachers to utilize ICT-based learning media in Banda Aceh is in the medium category. (total score = 170.22, this is in the range 140 ≤ X <220); and (2) There is a significant difference between the average of students interest in learning taught by high, medium and low competence teachers in utilizing ICT-based learning media. (F count = 40,205 with sig. = 0,000 <0,05).